2020
DOI: 10.3354/meps13166
|View full text |Cite
|
Sign up to set email alerts
|

Bulk tissue and amino acid stable isotope analyses reveal global ontogenetic patterns in ocean sunfish trophic ecology and habitat use

Abstract: C. (2020). Bulk tissue and amino acid stable isotope analyses reveal global ontogenetic patterns in ocean sunfish trophic ecology and habitat use. Marine Ecology Progress Series, 633, 127-140.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…It is possible that phytoplankton‐derived detritus either settled on the surface of macroalgae, or was utilized by epiphytes that were subsequently consumed by Aplodactylus . Alternatively, it may be a result of our undersampling of benthic microalgae, which is currently poorly characterized in terms of EAA δ 13 C (Phillips et al 2020). The suggested reliance of individuals of both Aplodactylus and Engraulis on Ulva presents more of a challenge to explain, as Ulva is not a dominant macroalgae at our sites in terms of biomass, although Aplodactylus are known to consume Ulva in large volumes when available (Caceres et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that phytoplankton‐derived detritus either settled on the surface of macroalgae, or was utilized by epiphytes that were subsequently consumed by Aplodactylus . Alternatively, it may be a result of our undersampling of benthic microalgae, which is currently poorly characterized in terms of EAA δ 13 C (Phillips et al 2020). The suggested reliance of individuals of both Aplodactylus and Engraulis on Ulva presents more of a challenge to explain, as Ulva is not a dominant macroalgae at our sites in terms of biomass, although Aplodactylus are known to consume Ulva in large volumes when available (Caceres et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Such an evolutionary constraint is supported by none of the known regionally endothermic fishes consuming a primarily gelativorous diet (Ates, 1988; Hetherington et al ., 2022), as well as the physiology and morphology of the largest gelativorous marine predators. The apparently ectothermic ocean sunfish Mola mola (Linnaeus 1758) (Watanabe & Davenport, 2021), which does not swim continuously (Nakamura et al ., 2015) because it is not an obligate ram ventilator as a predominantly gelata‐consuming adult (Phillips et al ., 2020), is the only other fish species with internalized red muscle (but powering the dorsal and anal fin) and no known retia (Davenport et al ., 2018). Similarly, the only homeothermic gelativore is the leatherback sea turtle Dermochelys coriacea (Vandelli 1761), which is thought to achieve that physiological capacity largely as a result of gigantothermy (Paladino et al ., 1990) and other advanced heat retention mechanisms (Davenport et al ., 2009; Greer et al ., 1973) in spite of a low metabolism consistent with ectothermic reptiles (Wallace & Jones, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As such, studies often use literature data on δ 13 C EAA fingerprints from natural and cultured primary producer collections to characterize resource utilization patterns of consumers across a wide range of systems. This approach relies on the assumption that normalized δ 13 C EAA fingerprints are robust to changing environmental conditions (e.g., Arthur et al 2014; MacDonald et al 2019; Phillips et al 2020). One of the only studies to rigorously test this concept was Larsen et al (2015), who found that normalizing δ 13 C AA values to their mean in a marine diatom species ( Thalassiosira weissflogii ) cultured across a range of light, salinity, temperature, and pH conditions significantly reduced δ 13 C AA variance.…”
Section: Discussionmentioning
confidence: 99%